Interpreting company reports and accounts : - Holmes, Geoffrey (Prentice Hall, 2005)
Interpreting Company Reports and Accounts guides the reader through the conventions and complexities of company accounts, explaining how to assess the financial and trading position of a company from year to year, how to spot undue risk taking and ¿¿cosmetic accounting¿¿ and where to look for clues on the quality of management. Packed with interesting real world examples, this is a highly practical book which shows readers how to analyse company reports and accounts, both qualitatively and quantitatively. The analysis is illustrated with over 200 extracts/examples from published accounts, ranging from BP and DIAGEO down to smaller companies on AIM